Does Foreign Direct Investment Increase the Productivity of Domestic Firms : In Search of Spillovers through Backward Linkages - Javorcik, Beata (World Bank, Washington, DC, 2014)
Many countries compete against one another in attracting foreign investors by offering ever more generous incentive packages and justifying their actions with the productivity gains that are expected to accrue to domestic producers from knowledge externalities generated by foreign affiliates. Despite this being hugely important to public policy choices, there is little conclusive evidence indicating that domestic firms benefit from foreign presence in their sector. It is possible, though, that researchers have been looking for foreign direct investment (FDI) spillovers in the wrong place. Multinationals have an incentive to prevent information leakage that would enhance the performance of their local competitors in the same industry but at the same time may want to transfer knowledge to their local suppliers in other sectors. Spillovers from FDI may be, therefore, more likely to take place through backward linkages-that is, contacts between domestic suppliers of intermediate inputs and their multinational clients-and thus would not have been captured by the earlier literature. This paper focuses on the understudied issue of FDI spillovers through backward linkages and goes beyond existing studies by shedding some light on factors driving this phenomenon. It also improves over existing literature by addressing several econometric problems that may have biased the results of earlier research. Based on a firm-level panel data set from Lithuania, the estimation results are consistent with the existence of productivity spillovers. They suggest that a 10 percent increase in the foreign presence in downstream sectors is associated with 0.38 percent rise in output of each domestic firm in the supplying industry. The data indicate that these spillovers are not restricted geographically, since local firms seem to benefit from the operation of downstream foreign affiliates on their own, as well as in other regions. The results further show that greater productivity benefits are associated with domestic-market, rather than export-oriented, foreign affiliates. But no difference is detected between the effects of fully-owned foreign firms and those with joint domestic and foreign ownership. The findings of a positive correlation between productivity growth of domestic firms and the increase in multinational presence in downstream sectors should not, however, be interpreted as a call for subsidizing FDI. These results are consistent with the existence of knowledge spillovers from foreign affiliates to their local suppliers, but they may also be a result of increased competition in upstream sectors. While the former case would call for offering FDI incentive packages, it would not be the optimal policy in the latter. Certainly more research is needed to disentangle these two effects.